Effect of heat stress on glutathione biosynthesis in wheat - Kocsy Gábor (Acta biologica Szegediensis, 2002)
A relationship was found between the frost sensitivity and glutathione accumulation during cold treatment in wheat. The aim of the present study was to investigate in the same genotypes whether there is also a relationship between the frost sensitivity and the glutathione accumulation during high temperature stress. The glutathione and hyroxymethylglutathione content as well as the activity of the two enzymes of glutathione synthesis was greater in the frost-sensitive genotypes than in the tolerant ones during heat stress. High temperature stress resulted in a greater ratio of the reduced to oxidised non-protein thiols and the greater glutathione reductase activity in the sensitive genotypes. Thus, it can be established that the GSH accumulation induced by heat stress depends on the frost sensitivity of wheat.